(untitled) (Eurasian Medical Research Periodical, 2022)
The present study aimed to assess the awareness of diabetic patients in Al-Qassim, Saudi Arabia, about the relationship between diabetes, oral health, and the COVID-19 pandemic. Materials and Methods: A cross-sectional questionnaire-based survey was conducted following systematic random sampling in four medical centers in Al-Qassim. Survey responses to 19 multiple choice questions were collected from 120 participants and subsequently analyzed